Plant salinity stress, sensing, and its mitigation through WRKY - Rai, Gyanendra Kumar; Mishra, Sonal; Chouhan, Rekha; Mushtaq, Muntazir; Chowdhary, Aksar Ali; Rai, Pradeep K.; Kumar, Ranjeet Ranjan; Kumar, Pradeep; Perez-Alfocea, Francisco; Colla, Giuseppe; Cardarelli, Mariateresa; Srivastava, Vikas; et al. (Frontiers in Plant Science, 2023)
Salinity or salt stress has deleterious effects on plant growth and development. It imposes osmotic, ionic, and secondary stresses, including oxidative stress on the plants and is responsible for the reduction of overall crop productivity and therefore challenges global food security. Plants respond to salinity, by triggering homoeostatic mechanisms that counter salt-triggered disturbances in the physiology and biochemistry of plants. This involves the activation of many signaling components such as SOS pathway, ABA pathway, and ROS and osmotic stress signaling. These biochemical responses are accompanied by transcriptional modulation of stress-responsive genes, which is mostly mediated by salt-induced transcription factor (TF) activity. Among the TFs, the multifaceted significance of WRKY proteins has been realized in many diverse avenues of plants’ life including regulation of plant stress response. Therefore, in this review, we aimed to highlight the significance of salinity in a global perspective, the mechanism of salt sensing in plants, and the contribution of WRKYs in the modulation of plants’ response to salinity stress. This review will be a substantial tool to investigate this problem in different perspectives, targeting WRKY and offering directions to better manage salinity stress in the field to ensure food security.